The EFFECT OF SERVICE QUALITY, PROMOTION AND RESTAURANT ATMOSPHERE ON CUSTOMER SATISFACTION AT SAILENDRA RESTAURANT - Tita Rohmatul Ummah; Darwin Saragih (LPPM Universitas Asa Indonesia, 2022)
The research was conducted with the aim of finding out the effect of service quality, promotion, and atmosphere on customer satisfaction at Sailendra Restaurant. Quantitative research with primary data is the method used in this study, the researchers distributed questionnaires at the first source to obtain primary data. While the method used in this research is multiple linear regression method. Then the results of this study are the quality of service has a positive and significant influence partially by 34.81% on customer satisfaction. Then the promotion has a positive and significant influence partially by 37.09% on customer satisfaction. Furthermore, the atmosphere has a positive and significant effect on customer satisfaction, and has a contribution of 29.71% to customer satisfaction. Quality of service, promotion, and atmosphere together have a significant influence of 46.3% on customer satisfaction. While the remaining 53.7% are influenced by other factors not included in this study.